PEMBUATAN BIOPORI UNTUK MENGURANGI MASALAH GENANGAN AIR DI DESA NYALABU DAYA KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN - Syaiful Arifin (P3M Politeknik Negeri Malang, 2020)
Nyalabu Daya Village is one of the dry areas where the soil has poor water absorption, or the amount of rainfall exceeds the soil's ability to absorb water. When it rains, what sometimes happens is a puddle of water that cannot be absorbed into the ground. Biopori is a solution to prevent flooding, a place for making organic waste, fertilizing plants, and improving the quality of groundwater. This service activity begins with the socialization of the importance of making biopore infiltration holes, how to make biopore holes, and determining the strategic points of biopore holes. Community service activities in the form of making biopores in Nyalabu Daya Village, Pamekasan District, Pamekasan Regency have been running successfully and are installed at several points. Villagers after knowing the benefits and ease of applying this biopore technology, many residents have independently installed biopori in the yard of their respective residents.